CHEMISTRY BEHIND DRUGS DISTRIBUTED BY THE POPULAR PHARMACY PROGRAM IN BRAZIL: SYNTHETIC ROUTES, STRUCTURE-ACTIVITY RELATIONSHIP AND FUTURE PERSPECTIVES - Dos Santos, Giovanny C. [UNESP]; Rodrigues, Julia L. [UNESP]; De Souza, Júllia R.; Da Silva-Filho, Luiz C. [UNESP]; Da Silva, Bruno H.S.T. (Sociedade Brasileira de Quimica (SBQ), 2021)
Certainly, most chemistry students, patients or simply curious, have already questioned themselves about certain medications present in their daily lives, trying to understand how they work and even how they can be obtained. Based on that, this work presents some known synthetic routes and the structure-activity relationship (SAR), of some active pharmaceutical ingredients present in medications distributed in Brazil by the government program known as Farmacia Popular, emphasizing the functional groups and chemical structure linked to their mechanisms of action. Some other characteristics and future perspectives of such drugs and their respective active principles are also highlighted.
A QUÍMICA POR TRÁS DOS MEDICAMENTOS DISTRIBUÍDOS PELO PROGRAMA FARMÁCIA POPULAR NO BRASIL: ROTAS SINTÉTICAS, RELAÇÃO ESTRUTURA-ATIVIDADE E PERSPECTIVAS FUTURAS
Keywords: Active pharmaceutical ingredient; Government program Popular Pharmacy; Medicinal organic chemistry; Organic synthesis; Popular medicines; SAR